Ultrasonic Assisted Extraction and Antimicrobial Activity of local Moringaoleifera leaves - Lamyaa Salih Mahdi,; Noor Salman Obaid,; Maysaa Saleh Mahdi,; Hasanain Shakir Mahmood, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Medicinal plants are attracting increasing interest due to their application in ethnomedicine to treat common ailments such as colds and fevers, where their therapeutic claims have been substantiated by strong scientific data. Investigation of medicinal plants has begun with extraction processes that significantly affect the extraction results (e.g., yield and phytochemical content) and subsequent experiments conducted. Ultrasound-assisted extraction (UAE) is a frequently used extraction method due to its efficiency in reducing extraction time and solvent usage. However, application of ultrasound energy above 20 kHz may affect the active phytochemicals by generating free radicals. Method: The leaves of Moringaolifera plant were dried under shade and then weighed. Ultrasound Assisted Extraction (UAE) method was carried out to extract the active compounds. Two samples each weight 15 g of M. oleifera dried leaves was extracted using 500 mL of both (Methanol: water 50:50) and petroleum ether (40–60) °C. The sonication conditions were UP400St ultrasonic processor for 10 min at room temperature. Two different polar aqueous methanolic extract and nonpolar organic petrulium ether extract weredried and subjected to phytochemical screening tests. GC-MS technique was utilised to characterize the nonpolar petrulium ether extract.After that, the antibacterial activity was examined against both gram positive (G +ve) and gram negative (G -ve) strains. Results: The phytochemical tests revealed the abundance of flavonoids, saponins, tannins, terpenes and alkaloids in the M. olifera extracts. Compounds like Fatty acids, aldehydes, Vitamin E and steroids as identified by GC-MS method. The current study, both aqueous methanolic and petroleum ether extracts in concentrations of 100, 200, 400, 800 µg/ml were verified against Gram positive G+ve and Gram negative G-ve bacteria. The results showed that methanol/water extract has been moderate to good effective in inhibition of G+ve bacteria S. aureus in tested concentration 200, 400, 800 µg\ml in comparison with gentamycin antibiotic while no effect was showed on G-ve bacteria E. coli. There was no antibacterial activity of petroleum ether extract on G+ve bacteria S. aureus in all tested concentration while it has a moderate effectiveness in G-ve bacteria E. coli on concentration 200 µg\ml this is suggested that it needs a particular concentration in order to give its activity. Conclusion: Moringaolifera is a promising plant in treating bacterial infection as it contains many important phytochemicals that can be extracted and isolated from it.